The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - and PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.